Aulenyl polysulfone anion exchange membrane as well as preparation method and application thereof
By using the new anion exchange membrane prepared by azaprol polysulfone polymer, the problem of degradation of the performance of anion exchange membrane under high temperature and alkaline conditions in the prior art is solved, and the effects of high OH-conductivity, alkaline stability and high mechanical strength are achieved.
Patent Information
- Application Number
- CN202411902034.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing anion exchange membrane fuel cells and alkaline electrolytic cells have deteriorated performance under high temperature alkaline conditions, and have low OH-conductivity, poor mechanical properties and short service life.
A new alkaline anion exchange membrane is prepared by polymerization and quaternization after polymerization, which improves its mechanical strength and alkalinity stability.
High OH-conductivity, alkaline stability and high mechanical strength are achieved, extending the service life of the film, and reducing water absorption and swelling rate.
Smart Images

Figure CN119735810A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology, and specifically relates to an azulene-based polysulfone anion exchange membrane and a preparation method and application thereof. Background Art
[0002] Over the past century, due to global development and population growth, energy demand around the world has continued to grow rapidly. The development of clean and efficient hydrogen energy is in line with the energy strategies of "carbon peak" and "carbon neutrality", and will help achieve sustainable development for mankind. Green hydrogen can be produced by water electrolysis technology driven by overcapacity "abandoned solar power, abandoned wind power and abandoned electricity", and fuel cells are the main application direction of hydrogen energy. At present, proton exchange membrane fuel cells and acidic electrolyzers operating under acidic conditions require the use of precious metal catalysts and expensive proton exchange membranes. The cost of producing and utilizing hydrogen is too high, and industrial development has been greatly hindered. Anion exchange membrane fuel cells and alkaline water electrolysis technology can use low-alkaline electrolytes and non-precious metal catalysts, which greatly reduces operating costs, and therefore have received widespread attention.
[0003] Anion exchange membrane (AEM) is a key component of anion exchange membrane fuel cells and alkaline electrolyzers. It is crucial to prepare anion exchange membranes with high hydroxide conductivity and stable chemical properties, so as to achieve high power density and long-term durability of anion exchange membrane fuel cells and alkaline electrolyzers. AEM is composed of a polymer skeleton, cationic groups and mobile ions. The properties of the polymer backbone structure and the cationic groups directly determine the performance of AEM. The research on AEM currently still faces the following technical bottlenecks: (1) Since the radius of OH- is larger than that of H+, the OH in AEM - The conductivity is only the H + The most direct way to improve conductivity is to increase the ion exchange capacity (IEC). The increase in IEC means the introduction of more hydrophilic cationic groups, which increases the water absorption rate of the membrane and increases the swelling, thus causing the mechanical properties of the membrane to decrease. Therefore, solving the "trade-off" effect between the ionic conductivity and dimensional stability of the membrane is crucial to the development of AEM. (2) Under hot alkaline working conditions, the polymer skeleton and cationic groups are susceptible to nucleophilic OH - The attack of ions causes complex degradation reactions of the main chain structure and cationic groups, which degrades the membrane performance and even reduces the service life of the AEM. Therefore, improving the alkaline stability of AEM and extending the service life of the membrane is another scientific problem that needs to be solved urgently. Summary of the invention
[0004] The present invention provides an azulene-based polysulfone anion exchange membrane, characterized in that the raw material of the azulene-based polysulfone anion exchange membrane is or contains an azulene-based polysulfone polymer, and its structure is shown in Formula 1:
[0005]
[0006] Wherein, R1 represents different types of cationic groups, R2 is a copolymer or branched monomer, a and b represent the molar content percentage of the two repeating units, the value of a is between 0-100 (the sum of the a values of the cross-linked polymer is between 0-100), the value of b is between 0-100, and a+b=100 (the value of a is preferably 15-50, more preferably 25).
[0007] In combination with the first aspect, preferably, the R1 is at least one of the following structures:
[0008]
[0009] Wherein, n is an integer greater than or equal to 0.
[0010] In combination with the first aspect, preferably, the R2 is at least one of the following structures:
[0011]
[0012] The present invention also provides a method for preparing the azulene-based polysulfone anion exchange membrane, the method comprising the following steps:
[0013] (1) Synthesis of azulene polysulfone precursor polymer: Synthesis of azulene polysulfone precursor polymer: Under alkaline catalysis conditions, diphenyl sulfone monomer, azulene monomer and monomer R2 are dissolved in organic solvents α and β in a certain proportion, and condensation reaction is performed to generate azulene polysulfone polymer (PSU-Az). PSU-Az polymer can be synthesized by three methods: DMAc / K2CO3, DMSO / NaOH and DMSO / KOH. The DMAc / K2CO3 method uses a one-step method to prepare the polymer: first, diphenol monomer, azulene monomer, K2CO3, DMAc and toluene are added to a dry three-necked flask in a certain proportion under N2 protection. Then, the mixture is heated to reflux at 140°C for 8 hours, and toluene and water are removed by azeotropic distillation. After the mixture is heated at 160°C for 12 hours, a viscous polymer solution is obtained. After cooling to room temperature, the viscous polymer solution was diluted with THF, and the diluted solution was poured into water to obtain a white fibrous polymer, which was then vacuum dried at 120°C for 24 hours to obtain the target product. The DMSO / KOH and DMSO / NaOH methods use a two-step method to prepare the polymer. The process is as follows: under N2 protection, diphenol monomer, K2CO3, DMAc and toluene are added to a dry three-necked flask in a certain proportion, refluxed at 140°C for 6 hours, and water is removed by azeotropic distillation. Then, the temperature is slowly raised to 160°C by controlling the removal of toluene from the reaction mixture. Subsequently, azulene monomer is added to the system, and the reaction time is about 1 hour at 160°C to obtain a viscous polymer solution. The following steps are the same as the treatment method of the DMAc / K2CO3 method.
[0014] The structure is shown in Formula II:
[0015]
[0016] Wherein, R1 represents a cationic group of different types, R2 is a copolymer or branched monomer, a and b represent the molar content percentage of the two repeating units, the value of a is between 0-100 (the sum of the a values of the cross-linked polymer is between 0-100), the value of b is between 0-100 (the sum of the b values of the cross-linked polymer is between 0-100, and a+b=100 (the value of a is preferably 15-50, more preferably 20-25); (2) Synthesis of cationized azulenyl polysulfone: The azulenyl polysulfone obtained in step 1 is dissolved in an organic solvent, potassium carbonate and iodomethane are added, and the reaction is stirred at room temperature in the dark for 24 hours. Ethyl acetate is added to the obtained viscous solution. After filtering the precipitate, it is washed with water three times, and the solvent is evaporated by vacuum drying to obtain a cationized azulenyl polysulfone;
[0017] (3) Preparation of azulene polysulfone anion exchange membrane: The cationized azulene polysulfone obtained in step 2 was dissolved in an organic solvent, stirred at room temperature and filtered, the filtrate was cast on a clean glass plate, the residual solvent was removed, and the film was carefully peeled off from the glass plate to obtain Cl - type membrane, and then Cl - The membrane was placed in KOH solution for ion exchange to obtain OH - The membrane was then washed with degassed deionized water under inert atmosphere to obtain an azulene polysulfone anion exchange membrane.
[0018] In a preferred embodiment of the present invention, in step (1), the molar ratio of the azulene monomer to the diphenol monomer in step (1) is 1:0.9-1.5.
[0019] In another preferred embodiment of the present invention, in step (1), the volume ratio of solvent α to solvent β is 1:0.8-1.2.
[0020] In another preferred embodiment of the present invention, in step (1), the organic solvent α is selected from at least one of DMSO, DMAc, DMF, or NMP.
[0021] In another preferred embodiment of the present invention, in step (1), the organic solvent β is selected from at least one of benzene, toluene, o-xylene, m-xylene, p-xylene, p-trimethylbenzene and m-trimethylbenzene.
[0022] In another preferred embodiment of the present invention, in step (2), the organic solvent is selected from at least one of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide or sulfolane.
[0023] The present invention also provides an azulene-based polysulfone anion exchange membrane prepared by the preparation method described above.
[0024] The present invention also provides a use of the azulene-based polysulfone anion exchange membrane in the preparation of a fuel cell or an alkaline electrolytic cell.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention synthesizes an azulene polysulfone polymer, and the material is polymerized and quaternized to prepare a novel alkaline anion exchange membrane. The polysulfone structure produces high mechanical strength, greatly reduces the water absorption and swelling rate of the anion exchange membrane, thereby improving the dimensional stability; at the same time, the highly stable cationic group nucleophilic azulene group increases its alkaline stability. Its high OH -The electrical conductivity, alkaline stability and high mechanical strength indicate that the azulene-based polysulfone anion exchange membrane obtained in the present invention can be used as anion exchange membrane material for alkaline fuel cells and alkaline electrolytic cells.
[0027] The azulene-based polybenzimidazole anion exchange membrane provided by the present invention exhibits high OH - Due to its high conductivity, alkaline stability and high mechanical strength, it can be used as anion exchange membrane material for alkaline fuel cells and alkaline electrolytic cells.
[0028] After optimization, the azulene-based polysulfone anion exchange membrane of the present invention has high OH - Electrical conductivity (80℃, OH - Conductivity>100mS cm -1 ), high mechanical strength (tensile strength>35MPa, elongation at break>10%), high dimensional stability, good processability, and excellent alkaline stability in 1M KOH at 80°C (>500h).
[0029] Compared with other types of branched poly(aryl-piperidine) anion exchange membranes, the strong dipole moment azulene groups and sulfur-containing main chains in its molecular structure contribute to the formation of a strengthened hydrogen bond network, promoting OH - The introduction of nucleophilic azulenyl groups makes the structure less susceptible to OH - attack, enhancing its alkaline stability; the formation of branched structure makes the molecular chains entangled with each other, enhancing its mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The synthetic route diagram of 6-6'-biazulene cross-linked poly 6-piperidinylazulene phenyl sulfone (PSU-Az-BiAz) provided in this application
[0031] Figure 2 The synthetic route diagram of poly (6-piperidinylazulene phenyl sulfone) (PSU-Az-Pd) provided in this application.
[0032] Figure 3 The present application provides a synthetic route diagram of poly (6-piperidinylazulene phenyl sulfone) (PSU-Az-Pr).
[0033] Figure 4 The commercial product FAA3-50OH of the azulene polysulfone anion exchange membrane prepared in Examples 1, 2 and 3 - Conductivity test results.
[0034] Figure 5 The test results of water electrolysis using the azulene-based polysulfone anion exchange membranes prepared in Examples 1, 2 and 3 and the commercial product FAA3-50 anion exchange membrane.
[0035] Figure 6These are the water absorption test results of the commercial product FAA3-50 azulene polysulfone anion exchange membrane prepared in Examples 1, 2 and 3.
[0036] Figure 7 These are the swelling rate test results of the commercial product FAA3-50 azulene polysulfone anion exchange membrane prepared in Examples 1, 2 and 3. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings. The described embodiments should not be regarded as limiting the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.
[0038] In the following description, reference is made to "some embodiments", which describe a subset of all possible embodiments, but it is understood that "some embodiments" may be the same subset or different subsets of all possible embodiments, and may be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present application have the same meaning as those commonly understood by those skilled in the art of the technical field of the embodiments of the present application. The terms used in the embodiments of the present application are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application.
[0039] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0040] It should be noted that all raw materials / reagents in the examples of the present application can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; the term "and / or" in the examples of the present application is only used to describe the association relationship between associated objects, indicating that three relationships may exist, for example, A and / or B means the existence of A alone, B alone, and A and B at the same time, among which A and B can be singular or plural, and the character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0041] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0042] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0043] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0044] Those skilled in the art will appreciate that the numerical ranges in the examples of the present application are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0045] Unless otherwise stated, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test cases of the present application. All documents mentioned in this specification are generally incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of the present application shall prevail.
[0046] It should be noted that all raw materials and / or reagents in the examples of the present application are purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0047] The following are the test methods used in the examples:
[0048] Performance Testing:
[0049] The equipment and testing methods involved in the embodiment are as follows:
[0050] Ion exchange capacity (IEC) test method: Take the Cl - Type or Br -The film was dried in a vacuum oven at 75°C and weighed, and the weight of the dry film was recorded. The dry film was soaked in 25 mL of 0.2 M NaNO3 solution for 6 hours, repeated three times, and the NaNO3 solution after ion exchange was collected. The indicator potassium chromate solution was added to the solution, and titrated with 0.01 M AgNO3 standard solution. When a brick-red precipitate appears and does not disappear after shaking, the titration is complete. Record the volume of AgNO3 solution consumed. The product of the concentration and volume of the AgNO3 solution divided by the mass of the dry film is the IEC.
[0051] Conductivity test: The electrochemical workstation used is produced by Shanghai Chenhua Instrument Co., Ltd., model CHI660E. The conductivity of the membrane at different temperatures was tested by the alternating current impedance method (EIS). The measured potential amplitude was 10mV. In order to reduce the error caused by the contact resistance to the measurement results, the resistance tested was the in-plane resistance of the membrane sample. In the experiment, the membrane was cut into a size of 40mm×10mm, placed in a fixture, and the fixture was placed in pure water. The test temperature was from 30℃ to 80℃, and the membrane resistance was tested every 10℃. It was necessary to keep warm for 1h before the test. Finally, the ionic conductivity σ of the sample was calculated according to the formula: σ=l / (wdR), where l is the length of the membrane between the electrodes (cm), w is the width of the membrane (cm), d is the thickness of the membrane (μm), and R is the measured membrane resistance (mΩ).
[0052] Water absorption test: The membrane was immersed in 1M KOH solution at a specific temperature for 6 hours (repeated four times), and the ions were exchanged for OH - Form. Wash with deionized water several times to remove residual KOH. After wiping off excess water on the surface, measure the wet mass (W wet,OH ). Then use formula (1) to calculate the water absorption (WU):
[0053] WU(%)=(W wet,OH -W dry,OH ) / W dry,OH × 100% (1)
[0054] Swelling rate (SR) measurement: According to the wet film (x wet ) and dry film (x dry ) is determined by the linear size difference between the PAP membranes and calculated according to formula (2):
[0055] SR(%)=(x wet -x dry ) xdry× 100% (2)
[0056] Alkaline fuel cell performance test: The instrument used is produced by Scribner Associates Co., USA, the instrument model is 850e multi-range fuel cell test system, and the test is carried out in current mode. The test conditions are full humidification of H2 and O2, test temperature of 60℃ and 80℃, and H2 and O2 flow rate of 200mL / min.
[0057] Anion exchange membrane water electrolysis performance test: anode is loaded with IrO2 (1mg / cm 2 ) titanium felt, the cathode is loaded with Pt / C (1 mg / cm 2 ) carbon paper, the electrode area is 4cm 2 The MEA electrolytic cell was assembled, the electrolyte was 1M KOH, the circulation rate was 20mL / min, and the test temperature was 60°C. The test instrument was CHI660e, and the electrolytic cell was subjected to a 0-2.5V linear voltammetric sweep test.
[0058] Tensile strength test: Instron M3300 electronic universal testing machine was used to test the dry film sample 5×0.5 cm (length×width) at a tensile rate of 5 mm / min.
[0059] Alkaline stability test: The prepared anion membrane was immersed in NaOH solutions of different temperatures and concentrations, and its conductivity was measured at the same time. The alkaline stability was analyzed by the change in the conductivity of the electrolyte membrane.
[0060] In a first aspect, an embodiment of the present application provides an azulene polysulfone anion exchange membrane, wherein the azulene polysulfone anion exchange membrane contains an azulene polysulfone polymer and has the following structure:
[0061]
[0062]
[0063] Wherein, R1 represents a cationic group of different types, R2 is a copolymer or branched monomer, a and b represent the molar content percentage of the two repeating units, the value of a is between 0-100 (the sum of the a values of the cross-linked polymer is between 0-100), the value of b is between 0-100 (the sum of the b values of the cross-linked polymer is between 0-100, and a+b=100 (the value of a is preferably 15-50, more preferably 20-25);
[0064] The azulene polysulfone anion exchange membrane provided in the embodiment of the present application is a basic anion exchange membrane prepared by polymerization and quaternization, wherein the strong dipole moment azulene group and the sulfur-containing main chain promote the formation of a strengthened hydrogen bond network, promoting OH -The branched structure produces high mechanical strength, greatly reducing the water absorption and swelling rate of the anion exchange membrane, thereby improving dimensional stability; at the same time, the high stability cationic group and nucleophilic azulenyl group increase its alkaline stability, and its high OH - The electrical conductivity, alkaline stability and high mechanical strength indicate that the polyazulene sulfide anion exchange membrane prepared in the present application can be used as anion exchange membrane material for alkaline fuel cells and alkaline electrolytic cells.
[0065] In a specific embodiment, R1 in the embodiment of the present application is preferably one of the following structures:
[0066]
[0067] Wherein, n is an integer greater than or equal to 0.
[0068] In a specific embodiment, R2 in the embodiment of the present application is preferably one of the following structures:
[0069]
[0070] In a second aspect, an embodiment of the present application provides a method for preparing the azulene-based polysulfone anion exchange membrane according to the first aspect, the preparation method comprising:
[0071] (1) Preparation of azulene polysulfone precursor:
[0072] The diphenol monomer, the azulene monomer and the branched monomer are placed in a reaction kettle, dissolved in a first mixed organic solvent, rapidly heated, reacted for a period of time, distilled to remove water, and after the reaction, the solid product is washed, dried and collected; the product is dissolved in a second organic solvent, potassium carbonate and iodomethane are added, reacted in the dark, ethyl acetate is added, purified, and the azulene polysulfone polymer is collected;
[0073] (2) Preparation of azulene polysulfone anion exchange membrane:
[0074] The cationized azulene polysulfone is dissolved in a third organic solvent, and the cationized azulene polysulfone is collected. - type film, so that the I - Type membrane for ion exchange to obtain OH - After purification, the azulene polysulfone anion exchange membrane was collected.
[0075] It should be noted that the azulene polysulfone precursor in the embodiment of the present application is prepared by the following method: first, an azulene monomer, a branching monomer and a diphenol monomer are placed in a reaction kettle in a certain proportion, dissolved in a first mixed organic solvent to obtain a mixed solution, the mixed solution is rapidly heated, and after a certain reaction time, water is distilled off and the reaction is continued. After the reaction is completed, the obtained solid product is collected, and the polymer solid is washed with deionized water and ethanol and dried to obtain an azulene polysulfone.
[0076] It should be noted that in the embodiment of the present application, collecting the azulene polysulfone polymer includes: filtering to obtain a solid polymer, washing it three times with deionized water, washing it once with anhydrous ethanol, and vacuum drying it.
[0077] There is no particular limitation on the drying conditions in the present application, as long as a product of constant weight can be obtained. In the examples of the present application, the drying temperature is preferably 80° C. and the drying time is preferably 24 h.
[0078] It should be noted that in the examples of the present application, the reaction was carried out at room temperature with stirring for 24 hours in the dark.
[0079] It should be noted that in the examples of the present application, the N atom in the azulene monomer reacts with methyl iodide to form a quaternary ammonium cation.
[0080] It should be noted that ethyl acetate in the examples of the present application serves as a good solvent for methyl iodide and can dissolve unreacted monomers. It also serves as a poor solvent for the polymer and causes the polymer to precipitate, thereby purifying the polymer.
[0081] In a specific embodiment, the molar ratio of the azulene monomer to the branched monomer in the embodiment of the present application is preferably 0-99:1.
[0082] Among them, when the molar ratio of the azulene monomer to the branching monomer is greater than 99:1, that is, when the content of the branching monomer is too low, the effect of the branching monomer on improving the performance of the anion exchange membrane is weak.
[0083] In a specific embodiment, the molar ratio of the sum of the added amounts of the branched monomer and the azulene monomer to the added amount of Na2S in the embodiment of the present application is preferably 1:0.9-1.2.
[0084] In a specific embodiment, the molar ratio of the sum of the added amounts of the branched monomer and the azulene monomer to Na2S in the embodiment of the present application is preferably 1:0.9-1.5.
[0085] Among them, when the molar ratio of the sum of the added amounts of branched monomers and azulene monomers to the diphenol monomer is less than 1:1.2, the local polymerization rate will be too fast, resulting in a too wide molecular weight distribution; when the molar ratio of the sum of the added amounts of branched monomers and azulene monomers to the diphenol monomer is greater than 1:0.9, the reaction yield and rate will decrease.
[0086] In a specific embodiment, the first mixed organic solvent in the embodiment of the present application is preferably a mixture of one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide and toluene.
[0087] The first mixed organic solvents are used to dissolve the reactants.
[0088] In a specific embodiment, the second organic solvent in the embodiment of the present application is preferably one of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide and cyclopentane.
[0089] The second organic solvents play a role in dissolving the polymer.
[0090] In a third aspect, embodiments of the present application provide a polyazulene sulfide anion exchange membrane as described in the first aspect, and use of the polyazulene sulfide anion exchange membrane prepared by the method as described in the second aspect in preparing alkaline fuel cells and alkaline electrolytic cells.
[0091] In a specific embodiment, the OH of the azulene polysulfone anion exchange membrane of the present application embodiment at 80°C - The conductivity is preferably at least 100 mS / cm.
[0092] The technical method of the present application will be further described below in conjunction with specific embodiments.
[0093] Example 1
[0094] Preparation of 6-6'-biazulene cross-linked poly 6-piperidinylazulene phenyl sulfone (PSU-Az-BiAz) anion exchange membrane:
[0095] (1) Synthesis of 6-6'-biazulene cross-linked poly (6-piperidinylazulene phenyl sulfone) (PSU-Az): The monomers 6-piperidinyl-1,3-dibromoazulene (10 mmol) and 1,3,1',3'-tetrabromo-6,6'-biazulene were prepared according to the literature (J.Org.Chem.2015,80,11513-11520 and Journal of Organic Chemistry 2019,84(3),1257-1275; Tetrahedron2006,62(48),11227-11239). 6-piperidin-1,3-dibromoazulene (9.5mmol), 1,3,1',3'-tetrabromo-6,6'-azulene (0.5mmol), bisphenol S (11mmol), potassium carbonate (15mmol) were added to dimethylacetamide (30mL) and toluene (25mL). The solution was refluxed at 140°C for 8h, and toluene and water were removed by azeotropic distillation. After continuing to react at 160°C for 12h, a viscous polymer was obtained. After the reaction system was cooled to room temperature, it was diluted with 25mL of tetrahydrofuran, and the solution was poured into water for sedimentation, and the resulting blue-black polymer fibers were collected; vacuum dried at 80°C for 24h to obtain PSU-Az-BiAz. The dried product was a black solid powder, a total of 7.2g, with a yield of 96.9%.
[0096] 1 g of the product was dissolved in 30 mL of dimethyl sulfoxide (DMSO), and then K2CO3 (0.39 g) and iodomethane (1 mL) were added, and the reaction was stirred at room temperature in the dark for 24 h. Ethyl acetate was added to the obtained viscous solution. The light yellow precipitate was filtered, washed three times with water, and vacuum dried in an oven at 80 ° C for 24 h to obtain PSU-Az-BiAz. The chemical structure of the polymer was determined by NMR and IR characterization. Figure 1 As shown, the weight average molecular weight is determined by GPC test to be 60 kDa (the molar ratio of a and b is 95:5, and the polymerization mode of the groups in brackets corresponding to a and b is random polymerization).
[0097] In order to facilitate the understanding of the synthesis process of the above-mentioned 6-6'-biazulene cross-linked poly 6-piperidinylazulene phenyl sulfone (PSU-Az-BiAz), the present application provides a synthesis route diagram of 6-6'-biazulene cross-linked poly 6-piperidinylazulene phenyl sulfone (PSU-Az-BiAz), as shown in FIG. Figure 1 As shown, Figure 1 The synthetic route diagram of 6-6' biazulene cross-linked poly (6-piperidinylazulene phenyl sulfone) (PSU-Az-BiAz) provided in this application.
[0098] (2) Preparation and ion exchange of PSU-Az-BiAz anion exchange membrane: PSU-Az-BiAz (1 g) was dissolved in 30 mL of DMSO, and the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter and cast on a clean glass plate. Subsequently, the solution was evaporated at 80°C for 12 h, evaporated at 120°C for 12 h, and vacuum dried at 120°C for 24 h to completely remove the residual solvent. I was peeled off from the glass plate. - The membrane was ion exchanged in 1M KCl solution at 80°C for 12 h, and then washed three times with deionized water to remove the residual salt and obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH - Type membrane.
[0099] Example 2
[0100] Preparation of poly 6-piperidinylazulene phenyl sulfone (PSU-Az-Pd) anion exchange membrane:
[0101] (1) Synthesis of poly (6-piperidinylazulene phenyl sulfone) precursor polymer (PSU-Az-Pd): The monomer p-6-piperidinyl-1,3-dibromoazulene was prepared according to the literature (J.Org.Chem.2015,80,11513-11520). p-6-piperidinyl-1,3-dibromoazulene (10 mmol), bisphenol S (10 mmol), and potassium carbonate (15 mmol) were added to dimethylacetamide (30 mL) and toluene (25 mL). The solution was refluxed at 140°C for 8 h, and toluene and water were removed by azeotropic distillation. After continuing to react at 160°C for 12 h, a viscous polymer was obtained. After the reaction system was cooled to room temperature, it was diluted with 25 mL of tetrahydrofuran, and the solution was poured into water for sedimentation, and the resulting blue polymer fibers were collected; and vacuum dried at 80°C for 24 h to obtain PSU-Az-Pd. The product after drying is a black solid powder, with a total of 7.5 g and a yield of 95.6%. 1 g of the product was dissolved in 30 mL of dimethyl sulfoxide (DMSO), and then K2CO3 (0.39 g) and iodomethane (1 mL) were added, and the reaction was stirred at room temperature in the dark for 24 hours. Ethyl acetate was added to the obtained viscous solution. After filtering the light yellow precipitate, it was washed three times with water and dried in a vacuum oven at 80°C for 24 hours to obtain PSU-Az-Pd. The chemical structure of the polymer was determined by nuclear magnetic resonance and infrared characterization. Figure 1 The weight average molecular weight was determined to be 65 kDa by GPC test (the molar ratio of a to b was 95:5, and the polymerization mode of the groups in brackets of a and b was random polymerization).
[0102] In order to facilitate the understanding of the synthesis process of the above-mentioned 6-piperidinylazulyl polysulfone (PSU-Az-Pd), the present application provides a synthesis route diagram of 6-piperidinylazulyl polysulfone (PSU-Az-Pd), such as Figure 2 As shown, Figure 2 The synthetic route diagram of 6-piperidinylazulyl polysulfone (PSU-Az-Pd) provided in this application.
[0103] (2) Preparation of poly PSU-Az-Pd anion exchange membrane:
[0104] PSU-Az-Pd (1 g) was dissolved in 30 mL DMSO, and the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter and cast on a clean glass plate. Subsequently, the solution was evaporated at 80 ° C for 12 h, evaporated at 120 ° C for 12 h, and vacuum dried at 120 ° C for 24 h to completely remove the residual solvent. The I-type membrane was peeled off from the glass plate. In 1M KCl solution, ion exchange was performed at 80 ° C for 12 h, and then washed with deionized water 3 times to remove the residual salt and obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH - type membrane, namely PSU-Az-Pd anion exchange membrane.
[0105] Example 3
[0106] Preparation of poly 6-pyrroloazulene phenyl sulfone (PSU-Az-Pr) anion exchange membrane:
[0107] (1) Synthesis of poly (6-piperidinylazulene phenylsulfone) precursor polymer (PSU-Az-Pr): The monomer p-6-pyrrole-1,3-dibromoazulene was prepared according to the literature (J.Org.Chem.2015,80,11513-11520). p-6-pyrrole-1,3-dibromoazulene (10 mmol), bisphenol S (10 mmol), and potassium carbonate (15 mmol) were added to dimethylacetamide (30 mL) and toluene (25 mL). The solution was refluxed at 140°C for 8 h, and toluene and water were removed by azeotropic distillation. After continuing to react at 160°C for 12 h, a viscous polymer was obtained. After the reaction system was cooled to room temperature, it was diluted with 25 mL of tetrahydrofuran, and the solution was poured into water for sedimentation, and the resulting blue polymer fibers were collected; vacuum dried at 80°C for 24 h to obtain PSU-Az-Pr. The product after drying is a black solid powder, with a total of 7.5 g and a yield of 95.6%. 1 g of the product was dissolved in 30 mL of dimethyl sulfoxide (DMSO), and then K2CO3 (0.39 g) and iodomethane (1 mL) were added, and the reaction was stirred at room temperature in the dark for 24 hours. Ethyl acetate was added to the obtained viscous solution. After filtering the light yellow precipitate, it was washed three times with water and dried in a vacuum oven at 80°C for 24 hours to obtain PSU-Az. The chemical structure of the polymer was determined by nuclear magnetic resonance and infrared characterization. Figure 1 The weight average molecular weight was determined to be 62 kDa by GPC test (the molar ratio of a to b was 95:5, and the polymerization mode of the groups in brackets of a and b was random polymerization).
[0108] In order to facilitate the understanding of the synthesis process of the above-mentioned 6-piperidinyl azulene polysulfone (PSU-Az-Pr), the present application provides a synthesis route diagram of 6-piperidinyl azulene polysulfone (PSU-Az-Pr), such as Figure 3 As shown, Figure 3 The synthetic route diagram of 6-piperidinylazulyl polysulfone (PSU-Az-Pr) provided in this application.
[0109] (2) Preparation of poly PSU-Az-Pr anion exchange membrane:
[0110] PSU-Az (1 g) was dissolved in 30 mL DMSO, and the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter and cast on a clean glass plate. Subsequently, the solution was evaporated at 80 ° C for 12 h, evaporated at 120 ° C for 12 h, and vacuum dried at 120 ° C for 24 h to completely remove the residual solvent. The I-type membrane was peeled off from the glass plate. In 1M KCl solution, ion exchange was performed at 80 ° C for 12 h, and then washed with deionized water 3 times to remove the residual salt and obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH- type membrane, namely PSU-Az-Pr anion exchange membrane.
[0111] In order to verify the performance of the azulene-based polysulfone anion exchange membrane prepared in Examples 1-3, performance tests were performed on the azulene-based polysulfone anion exchange membrane and a commercial FAA 3-50 anion exchange membrane. The test results are shown in the figure.
[0112] The test results show that the PSU-Az-BiAz anion exchange membrane prepared in Example 1 has a thickness of 60 μm and an OH - The conductivity is 150mS / cm, the ion exchange capacity is 2.5mmol / g, the swelling rate is 20%, the water absorption rate is 46%, the tensile strength is 70MPa, the elongation at break is 15%, and the alkaline stability is maintained for 1000h in 1M KOH at 80℃, and there is no obvious decomposition of the polymer film during this process. - The conductivity is 140mS / cm, the ion exchange capacity is 2.3mmol / g, the swelling rate is 22%, the water absorption rate is 46%, the tensile strength is 55MPa, the elongation at break is 12%, and the alkaline stability is maintained for 1000h in 1M KOH at 80℃. During this process, the polymer film has no obvious decomposition phenomenon. The PSU-Az-Pr anion exchange membrane prepared in Example 3 has a thickness of 60 microns and is hydrated at 80℃. - The conductivity is 138mS / cm, the ion exchange capacity is 2.1mmol / g, the swelling rate is 25%, the water absorption rate is 48%, the tensile strength is 50MPa, the elongation at break is 10%, and the alkaline stability is maintained for 1000h in 1M KOH at 80°C. During this process, the polymer film has no obvious decomposition phenomenon; this shows that the homogeneous anion exchange membrane prepared in this embodiment has less swelling, suitable ion conductivity and anion exchange capacity, and good mechanical properties; and with the addition of branched monomers, OH - The conductivity is increased, the swelling rate is reduced, and the mechanical properties are enhanced. At the same time, the polyazulene sulfide anion exchange membrane prepared in the example is superior to the commercial FAA 3-50 anion exchange membrane in terms of conductivity and anion exchange membrane water electrolysis performance.
[0113] Figure 4 The commercial product FAA3-50OH of the azulene polysulfone anion exchange membrane prepared in Examples 1, 2 and 3 - Conductivity test results.
[0114] Figure 5 The test results of water electrolysis using the azulene-based polysulfone anion exchange membranes prepared in Examples 1, 2 and 3 and the commercial product FAA3-50 anion exchange membrane.
[0115] Figure 6 These are the water absorption test results of the commercial product FAA3-50 azulene polysulfone anion exchange membrane prepared in Examples 1, 2 and 3.
[0116] Figure 7 These are the swelling rate test results of the commercial product FAA3-50 azulene polysulfone anion exchange membrane prepared in Examples 1, 2 and 3.
[0117] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. An azulene-based polysulfone anion exchange membrane, characterized in that: The raw material of the azulene-based polysulfone anion exchange membrane is or contains an azulene-based polysulfone polymer, and its structure is at least one or more of the following as shown in Formula 1: Formula 1 Linear azulene-based polysulfone (R2 is a two-arm or two-connected monomer) Formula II cross-linked azulenyl polysulfone (R2 is a monomer containing four arms or four connecting positions) wherein: R1 represents different types of cationic groups, R2 is a copolymer or branched monomer, a and b represent the molar percentage of the two repeating units, the value of a is between 0-100 (the sum of the a values of the cross-linked polymer is between 0-100), the value of b is between 0-100 (the sum of the b values of the cross-linked polymer is between 0-100, and a+b=100 (the value of a is preferably 15-50, more preferably 20-25); R1 is at least one or two or more of the following structures: In the group R1, n is an integer greater than or equal to 0 (preferably 1-8, more preferably 5-8) and R2 is at least one or two or more of the following structures: The wavy lines in the above structure Represents a connection, including two wavy lines Indicates that the monomer used is a two-arm or two-connection monomer, with four wavy lines Representative monomers used are four-arm or four-linked monomers.
2. The azulene-based polysulfone anion exchange membrane according to claim 1, characterized in that: The weight average molecular weight of the azulene-containing polysulfone polymer of formula I is in the range of 1.0-10.0 kda; the film thickness is 10-200 μm, a and b represent the molar content percentage of the two repeating units, the value of a is between 0-100 (the sum of the a values of the cross-linked polymer is between 0-100), the value of b is between 0-100, and a+b=100 (the value of a is preferably 15-50, more preferably 20-25); the polymerization mode of the groups in the brackets of a and b is random polymerization; To ensure film-forming properties, the cross-linking monomer corresponding to the R2 group is a two-arm or two-connected monomer, or a combination of a two-arm or two-connected monomer and a four-arm or four-connected monomer. When a combination of a two-arm or two-connected monomer and a four-arm or four-connected monomer is used, the molar content percentage of the four-arm or four-connected monomer in (the two-arm or two-connected monomer and the four-arm or four-connected monomer) is 0.01%-10%.
3. A method for preparing the azulenyl polysulfone anion exchange membrane according to claim 1 or 2, characterized in that: The following steps are involved: (1) Synthesis of azulenyl polysulfone precursor polymer: Under alkaline catalytic conditions, diphenyl sulfone monomer (bisphenol S) and azulene monomer (specific structure or name may be 1,3-dibromo-6-piperidinazulene, 1,3-dibromo-6-pyridinazulene, 1,3-dibromo-6-pyrroloazulene, 1,3-dibromo-6-tetrahydropyrroloazulene, etc., which are one or more of the corresponding azulene monomers in claim 1) are dissolved in organic solvents α and β in a desired proportion, and condensed to form an azulene polysulfone polymer (PSU-Az); PSU-Az polymers can be synthesized using one of three methods: N,N-dimethylacetamide / potassium carbonate (DMAc / K2CO)3, dimethyl sulfoxide / sodium hydroxide (DMSO / NaOH), or dimethyl sulfoxide / potassium hydroxide (DMSO / KOH); The DMAc / K2CO3 method adopts a one-step method to prepare a polymer: first, under the protection of N2, diphenol monomer, azulene monomer, K2CO3, DMAc and toluene are added to a dry container in a certain proportion; then, the mixture in the container is heated to reflux at 120-140°C (preferably 130-140°C) for 4-12h (preferably 7-10h), and toluene and water are removed by azeotropic distillation; the mixture is further heated at 160-180°C (preferably 160-170°C) for 8-18h (preferably 10-14h) to obtain a viscous polymer solution; after cooling to room temperature, the viscous polymer solution is diluted with THF, and the diluted solution is poured into water to obtain a blue-black fibrous polymer, which is then vacuum dried at 80-120°C (preferably 110-120°C) for 16-48 hours to obtain the target product; The DMSO / KOH and DMSO / NaOH methods respectively adopt a two-step method to prepare the polymer, and the process is as follows: under N2 protection, diphenol monomer, KOH or NaOH, DMAc and toluene are added to a dry container in a certain proportion, refluxed at 120-140°C (preferably 140°C) for 4-10 hours (preferably 5-7 hours), water and toluene are removed by azeotropic distillation, and the temperature is slowly raised to 160-180°C (preferably 160-170°C); then, an azulene monomer is added to the system, and the reaction time is 0.5-2 hours at 160-180°C (preferably 160-170°C) to obtain a viscous polymer solution; after cooling to room temperature, the viscous polymer solution is diluted with THF, and the diluted solution is poured into water to obtain a blue-black fibrous polymer, and then vacuum dried at 80-120°C (preferably 110-120°C) for 16-48 hours to obtain the target product; The structure is shown in Formula I: (2) Synthesis of cationized azulenyl polysulfone: dissolve the azulenyl polysulfone obtained in step 1 in an organic solvent δ, heat to dissolve it, add an excess of a γ reagent with a cationic group, heat in a dark place (room temperature - 120°C, preferably 60-80°C) and stir to react; put the obtained solution into water for precipitation, wash the obtained solid with water, and dry; (3) Preparation of azulene polysulfone anion exchange membrane: dissolve the cationized azulene polysulfone obtained in step (2) in an organic solvent, stir and filter at room temperature, cast the filtrate on a flat plate (such as a glass plate), heat to 40-80° C. (preferably 60-80° C.) to remove the solvent, and then peel off the film from the plate to obtain Cl - Br - or I - type membrane, and then Cl - Br - or I - The membrane is placed in KOH solution for ion exchange to obtain OH - The membrane is then washed with water under an inert atmosphere (such as nitrogen) to obtain an azulene polysulfone anion exchange membrane.
4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of the azulene monomer to the diphenyl sulfone monomer is 1:0.9-1.2, preferably 1:1.05-1.
1.
5. The preparation method according to claim 3, characterized in that: In step (1), the volume ratio of solvent α to solvent β is 1:0.8-1.2, preferably 1:1; The organic solvent α is selected from at least one or more of DMSO, DMAc, N,N-dimethylformamide (DMF), or N-methylpyrrolidone (NMP); The organic solvent β is selected from at least one or more of benzene, toluene, o-xylene, m-xylene, p-xylene, p-trimethylbenzene and m-trimethylbenzene.
6. The preparation method according to claim 3, characterized in that: In step (2) or (3), the organic solvent δ is selected from at least one or more of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide or sulfolane; In step (2), the solid content of azulenyl polysulfone dissolved in organic solvent β is 0.01-50wt% (preferably 3-7wt%), The heating dissolution temperature is 20-120°C (preferably 60-80°C); the ratio of the γ reagent to the azulene polysulfone is 0.1-100:1, and the reaction is stirred at room temperature in the dark for 1-100 hours; the γ reagent is one or more of the following structures: CH3X, Wherein, X is Cl, Br or I, and n is an integer greater than or equal to 0 (preferably 0-8, more preferably 5-8).
7. Use of the azulenyl polysulfone anion exchange membrane according to claim 1 or 2 or the azulenyl polysulfone anion exchange membrane prepared by the preparation method according to any one of claims 3 to 6 as a diaphragm in a fuel cell or an alkaline electrolytic cell.
Citation Information
Patent Citations
Chemically resistant membranes, coatings and films and methods for their preparation
CN102405094A
Polymeric ionomer separation membranes and methods of use
CN107921370A
Aulenyl branched poly (aryl-piperidine) anion exchange membrane as well as preparation method and application thereof
CN118562101A
Anion exchange membranes, methods of preparation and uses
US20130292252A1
Sensitized decomposition of polysulfone resists
US3916036A